Muscular postural behaviour in the shoulder girdle, during reaching at two different distances, performed by young adults born premature and at term - Castro, Beatriz Marques de (2021)
Premature birth is associated with changes in the maturation processes of neuronal systems, including those responsible for postural control and anticipatory postural adjustments, even in the absence of lesiono f the Central Nervous System. Although the literatura indicates that these changes may persist in older children and/or adolescentes, it remains nuclear whether they are still observable in adults born preterm. This study aimed to compare the behaviour of postural muscles in the shoulder gridle, namely the timing and amplitude of activation of the muscle’s serratus anterior, lower and upper trapezius, during reaching at two diferente distances, performed by young adults born premature anda t term. The timing and the amplitude of muscular activation were assessed in 14 young adults born premature and 14 born at term, through the analysis of the electromyographic activity of the serratus anterior, lower and upper trapezius ipsilaterally to the movement, as they reached for a bottle with both upper limbs separately. This task was performed at two diferente distances, at the functional length and at the maximal length of the arm. In general, muscles did not activate in the time window of anticipatory postural adjustments considered. The serratus anterior showed a delay in its timing of activation and the lower trapezius amplitude of activation was higher, in the preterm group. It was also found that the serratus anterior activated with higher amplitudes in the functional gesture for both groups. In the preterm group, the amplitude of activation of the lower trapezius was higher in the functional reach, and the same was observed in the upper trapezius in the maximal length of the arm movement. The results if this study suggest that, in young adults born prematurely, it is possible to detect diferences in activation of postural muscles, in the shoulder girdle, during reaching gesture at two diferente distances, when compared with their peers born at term.